How do primary education students learn to take diversity into consideration? - Gallego Ortega, José Luis; Rodríguez Fuentes, Antonio (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
The article contains a reflection based on traditional and current training needs of teachers, in their initial training period, to meet the challenge of attending to diversity in the context of the current Inclusive School. To support the specific personal proposal made claims and demands are reviewed in this area and they are placed in the new teacher training scenario drawn by the EEES: Degrees of Teachers (Infant and Primary Education) and PostGraduate Studies (Inclusive School). Recent (Inclusive education) and bright (emerging degrees) changes justifying the opportunity of this speech, whose result is a statement of intentions for college and university professors in order to optimize the current initial training of teachers to enable them the effective care of the specific needs of their future students.